Assessment of Antisickling Properties of Extracts of Plants used in the Traditional Treatment of Sickle Cell Disease in Benin - Avaligbe, C. T.; GBENOU, Joachim; KPOVIESSI, Dossou Sika Salomé; Gbaguidi, A. Fernand; MOUDACHIROU, Mansourou; Accrombessi, Georges C.; Gbeassor, M. (My University, 2012)
The purpose of this study is to value the in vitro anti-sickling activity of aqueous extracts of six plants used in the treatment of the sickle cell disease in Benin: Morinda lucida, Uvaria chamae, Lonchocarpus cyanescens, Croton zambesicus, Raphiostylis beninensis and Xylopia aethiopica. A decrease in the rate of sickling was observed after incubation of erythrocytes with plant extracts and 2% sodium metabisulfite as compared to incubation with 0.9% NaCl. The results of the study about the inhibitory properties of the SS erythrocytes sickling by the aqueous extract of the mixture of Raphiostylis beninensis, Croton zambesicus, Lonchocarpus cyanescens, Uvaria chamae, Morinda lucida and Xylopia aethiopica show that it has an obvious antisickling effect in vitro according to our experimental conditions (sickling inhibition rate > 50%). It is the same with aqueous extracts of Uvaria chamae, Morinda lucida and Xylopia aethiopica which inhibit more than 45% of SS erythrocytes sickling. Antisickling effects of those last plants on AS and SS erythrocytes are otherwise highly correlated ("r " is respectively equal to 0,88; 0,88 and 0,66). The extract of Raphiostylis beninensis, Croton zambesicus and Lonchocarpus cyanescens have relatively less effect (inhibition rate < 21%) particularly on SS erythrocytes sickling and a correlation coefficient "r" respectively equal to -0,2353; 0,3959 and 0,723. Our results point out that these six plants have, at different doses, an obvious antisickling effect in vitro and support the interest of their use in the traditional treatment of sickle cell disease.
Keywords: Sickle cell disease-Sickling-Morinda lucida-Uvaria chamae-Lonchocarpus; cyanescens-Croton zambesicus-Raphiostylis beninensis-Xylopia aethiopica